Karyotype and nucleolus organizer regions of ophisternon aenigmaticum (teleostei: Synbranchiformes: Synbranchidae) from venezuela (in english) - Nirchio, Mauro [UNESP]; Mariguela, Tatiane Casagrande [UNESP]; Ferreira, Irani Alves [UNESP]; Foresti, Fausto [UNESP]; Oliveira, Claudio (My University, 2011)
The first cytogenetic analysis by conventional Giemsa staining, silver nitrate impregnation of nucleolus organizer regions (Ag-NOR), and fluorescence in situ hybridization (FISH) carried out on Ophisternon aenigmaticum from Margarita Island, Venezuela, is reported. Two cytotypes were found: cytotype C1, 2n=46, composed of 6 medium size metacentrics, 2 subtelocentrics and 38 acrocentrics; and cytotype C2, 2n=45, composed of one large metacentric plus 5 medium size metacentrics, 1 subtelocentric and 38 acrocentric chromosomes. In cytotype C1, major ribosomal DNA (rDNA) cistrons are located in the terminal position of the short arms of the first metacentric pair as determined by Ag-NORs and FISH with the 18S rDNA probe. In cytotype C2, silver staining revealed only one positive signal in a single chromosome of the pair 1 whereas FISH with the 18S rDNA probe hybridized in two different chromosomes: One coincident with the Ag-NOR (pair 1) and other in one acrocentric chromosome, suggesting the occurrence of a peri-centric inversion. In both cytotypes, FISH with 5S rDNA probe produced hybridization signals in subtelomeric position of the short arm of the chromosome pair No. 3. Chromosome evolution in Synbranchidae is discussed.
Keywords: 18S DNA; 5S rDNA; Chromosome Evolution; Chromosome Fusion; Fish Chromosome; Pericentric Inversion